Quality of Life of Patients with Mandibular Third Molars and Mild Pericoronitis. A Comparison between Two Different Treatments: Extraction or Periodontal Approach - P. C. Passarelli; M. A. Lopez; V. Desantis; G. B. Piccirillo; E. Rella; V. Giovannini; A. Speranza; M. De Leonardis; P. F. Manicone; M. Casale; A. D'Addona (MDPI AG, 2020)
Background: The extraction of the mandibular third molar is one of the most frequent intervention in oral surgery. A common indication for wisdom tooth extraction is represented by pericoronitis, which can determine discomfort and pain in patients. The present study aimed to evaluate the impact of patients' quality of life by comparing a surgical approach with a periodontal approach. Methods: We evaluated 82 patients diagnosed with pericoronitis that occurred at the third molar site. In total, 41 of them received a periodontal treatment and 41 were treated by extraction. The quality of life (QoL) of the patients was assessed by using the Oral Health Impact Profile-14 (OHIP-14) index. Results: A total of 82 patients were included in the study and were followed up for 6 months. Of the patients, 41 received a periodontal treatment and 41 underwent surgical extraction. At the baseline, the OHIP-14 scores of the surgical group were higher (19.71, SD 9.90) than the periodontal group (14.41, SD 8.71). At 1 week, there was a reduction in terms of OHIP-14 in both groups, but the periodontal group showed lower values (12.3, SD 8.11). Long-term follow-up showed a reduction of the OHIP-14 values, with a difference in favor of the surgical group (0.10, SD 0.45). However, there was a reduction in OHIP-14 scores in both groups. Conclusion: Although the periodontal treatment offered a rapid improvement in terms of quality of life during the first week after the treatment, after 1 month and 6 months, the extraction of the mandibular third molar extraction remained the best treatment, removing the occurrence of re-inflammation of the site.